2012
DOI: 10.1364/ol.37.002292
|View full text |Cite
|
Sign up to set email alerts
|

Multiwatt octave-spanning supercontinuum generation in multicore photonic-crystal fiber

Abstract: High-power supercontinuum spanning over more than an octave was generated using a high power femtosecond fiber laser amplifier and a multicore nonlinear photonic crystal fiber (PCF). Long multicore PCFs (as long as 20 m in our experiments) are shown to enable supercontinuum generation in an isolated fundamental supermode, with the manifold of other PCF modes suppressed due to the strong evanescent fields coupling between the cores, providing a robust 5.4 W coherent supercontinuum output with a high spatial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…For our seven-core PCFs with the filling ratio beyond 0.6, high order supermodes can exist in the seven-core region without doubt, as reported in ref. [17]. To make it clear, we also intentionally checked the mode change at bending diameter of 10 mm for the PCFs, and found that the output beams remain at good performance.…”
Section: Mode Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…For our seven-core PCFs with the filling ratio beyond 0.6, high order supermodes can exist in the seven-core region without doubt, as reported in ref. [17]. To make it clear, we also intentionally checked the mode change at bending diameter of 10 mm for the PCFs, and found that the output beams remain at good performance.…”
Section: Mode Propertymentioning
confidence: 99%
“…3) Maintaining high beam quality output through the beam coherent combination effect by careful design of structure parameters [15], [16]. In 2012, X. H. Fang firstly reported a 5.4 W SC output from a 20-m-long seven-core PCF pumped by space coupling method, covering range from 500 to 1700 nm with a high spatial and spectral quality [17]. H. F. Wei subsequently reported a 42.3 W all-fiber SC source with coverage from 720 to 1700 nm from the 20-mlong seven-core PCF [18] with the zero dispersion wavelength (ZDW) at 1115 nm.…”
mentioning
confidence: 99%
“…Multicore PCFs offer a possibility of scaling up the mode field area to a large extent without a remarkable change in dispersion properties which show great potential in highpower supercontiuum generation. 7,8 As shown in Ref. 7, 5.4-W SC spanning from 500 to 1700 nm was generated using a high-power femtosecond fiber amplifier with a central wavelength of 1038 nm and a seven-core nonlinear PCF with an air-filling fraction 0.55 where each core diameter was 3.8 μm and there was a zero dispersion wavelength (ZDW) of the in-phase supermode 1025 nm.…”
Section: Introductionmentioning
confidence: 99%
“…These fibers would have potential applications in optical sensors [3], [4] and in space division multiplexing for improving channel capacity of optical fiber communication systems [5]. One of the problems associated with the use of MCFs is the lack of proper fiber components for efficient light coupling (splitting and combining).…”
Section: Introductionmentioning
confidence: 99%